PERTANGGUNGJAWABAN PIDANA DEBT COLLECTOR YANG MELAKUKAN TINDAK PIDANA TERHADAP DEBITUR LAYANAN APLIKASI PINJAMAN ONLINE - Sari Nilam Cayo, Putri (Justici, 2023)
ABSTRACT Online lending is the implementation of financial services which is a place for lenders and loan recipients to meet in order to carry out loan agreements using the rupiah currency using an electronic system, namely the internet network. Online loans can also be interpreted as financing or lending services provided by certain bodies online or in a network. The problem that the author will discuss is regarding how the criminal responsibility of Debt Collectors who commit crimes against debtors of online loan application services. In the event that the debt collector uses harsh words and is done in public, then he can be punished with an insult article, namely article 310 of the Criminal Code: "Whoever damages the honor or reputation of a person by accusing him of doing something with real intentions will be broadcast on this charge, is punished for blasphemy, with a maximum prison sentence of nine months or a maximum fine of Rp. 4500”.